English Education Students’ Perception on the Use of Elena in the Post-Pandemic Era - Ummi Nur Laila Sulistyani (English Education Journal, 2023)
Elena, an e-learning aid based on MOODLE version 2.0 developed by Universitas Negeri Semarang, is used to support the teaching and learning process as a response to the post COVID-19 outbreak. In English Education study program, Elena is mostly used not only for the lecturer to upload the materials, but also for the students to have discussion session, do assignment, exam, and quiz. However, as we shift from full online classes to ofline classes, it is important for all the parties and stakeholders to re-evaluate the use of Elena in teaching and learning process in post pandemic era, especially for students as the main user. A descriptive study was conducted by giving questionnaire and having in-depth interview to 100 students who participated. The results shows that students have positive perception towards the use of Elena in post-pandemic era to support the teaching and learning process, especially in learning language. However, some improvement such as make Elena into application rather than web-based learning aid, improve the user interface, and add live notification synchronized into students’ Telegram bot or MyUNNES should be considered.